Multidisciplinary Approaches to Hospital Preparedness and Management of Infectious Disease Outbreaks in Saudi Arabia-Hepatitis as an Example - Khairi, Ahmed Mohammed Ali; Ali Gerardi, Ahmad Al Jaafari; Duaa Thiyabi Yahya Hakami; Bayan Abdullah Alahmadi; Talal Saud Hulayyil Alanazi; Nasser Abdulsalam Nasser Alyemni; Abdulaziz Mansour Saad Algrni; Bader Gabreel Jaber Abdali; Gazala Musa Ali Mahmoud; Faisal Ali Ali mujarrbi; et al. (Saudi Journal of Medicine and Public Health, 2025)
Background: Viral hepatitis remains a major public health concern in Saudi Arabia, with varying epidemiology across hepatitis A, B, C, D, and E. Despite substantial progress achieved through nationwide vaccination, improved sanitation, surveillance, and treatment programs, challenges persist due to demographic shifts, behavioral risk factors, co infections, and disparities in healthcare access. Aim: This review aims to synthesize current evidence on the epidemiology, risk factors, prevention strategies, and management of viral hepatitis in Saudi Arabia, while highlighting the multidisciplinary roles essential to preparedness and outbreak control. In the same way, this review aims to evaluate the main role of physician, epidemiologists, internal specialists, nutritionists, health security professionals, medical information technologists, medical secretaries, medical managers, and physiotherapists in the management of hepatitis during outbreaks. Methods: A narrative review approach was utilized, analyzing national surveillance reports, seroprevalence studies, Ministry of Health publications, and published regional data addressing HAV–HEV distribution, determinants, and clinical management strategies across healthcare sectors in Saudi Arabia. Results: Findings demonstrate significant declines in HBV prevalence due to universal infant vaccination, fluctuating HAV and HEV incidence influenced by sanitation and seasonal patterns and marked reductions in HCV linked to the National Hepatitis Program and direct acting antivirals. HDV remains underdiagnosed but clinically significant among HBV carriers. Risk factors include socioeconomic disparities, inadequate sanitation, unsafe medical practices, intravenous drug use, and limited adult vaccination uptake. Management strategies vary by viral type, with strong national programs supporting HBV and HCV control, though HDV and HEV treatment access remain limited. Conclusion: Saudi Arabia has achieved substantial progress in hepatitis control through vaccination, surveillance, and treatment programs. However, persistent gaps—particularly in stigma reduction, adult vaccination, HDV surveillance, and access disparities—require strengthened integrated strategies and multidisciplinary collaboration.